Factors Affecting Sexual Relations in Third Trimester Pregnant Women at Batua Health Center Makassar City - Nur Ismi Wahyuni (Pusat Riset dan Inovasi Nasional, 2021)
Sexual intercouse during pregnancy is not just an ordinary but useful activity as a pelvic floor preparation for labor. Health care efforts undertaken to alter the public view of sexual activity during pregnancy is to provide careful and precise service The purpose of this study was to determine the factors that influence sexual relations in pregnant women Trimester III at Puskesmas Batua Kota Makassar Year 2018. Data analysis was performed by Chi-square test. This research use Analytic Survey design with cross sectional Study approach. The sample size in this research is 23 people. Sampling was done using Purposive sampling. This research was conducted at Puskesmas Batua Kota Makassar Year 2018. From result of statistical analysis concluded there is significant influence between pregnant woman's anxiety with sexual relationship where (value p = 0,021), there is significant correlation between physical condition of pregnant woman with intercourse where (p value = 0,006) and there is significant relation between knowledge of pregnant women with intercourse where (p value = 0,005). Therefore, the puskesmas is expected to add information to the public, especially pregnant women about sexual relations of pregnant women trimester III and for pregnant women do not think negatively about pregnancy.